Single-cell analysis of prostaglandin E2-induced human decidual cell in vitro differentiation: a minimal ancestral deciduogenic signal. Issue 1 (30th September 2021) - Stadtmauer, Daniel J; Wagner, Günter P
Abstract: The decidua is a hallmark of reproduction in many placental mammals. Differentiation of decidual stromal cells is known to be induced by progesterone and the cyclic AMP/protein kinase A (cAMP/PKA) pathway. Several candidates have been identified as the physiological stimulus for adenylyl cyclase activation, but their relative importance remains unclear. To bypass this uncertainty, the standard approach for in vitro experiments uses membrane-permeable cAMP and progestin. We phylogenetically infer that prostaglandin E2 (PGE2 ) likely was the signal that ancestrally induced decidualization in conjunction with progesterone. This suggests that PGE2 and progestin should be able to activate the core gene regulatory network of decidual cells. To test this prediction, we performed a genome-wide study of gene expression in human endometrial fibroblasts decidualized with PGE2 and progestin. Comparison to a cAMP-based protocol revealed shared activation of core decidual genes and decreased induction of senescence-associated genes. Single-cell transcriptomics of PGE2 -mediated decidualization revealed a distinct, early-activated state transitioning to a differentiated decidual state. PGE2 -mediated decidualization was found to depend upon progestin-dependent induction of PGE2 receptor 2 (PTGER2) which in turn leads to PKA activation upon PGE2 stimulation. Progesterone-dependent induction of PTGER2 is absent in opossum, an outgroup taxon of placental mammals which is incapable of decidualization. Together, these findings suggest that the origin of decidualization involved the evolution of progesterone-dependent activation of the PGE2 /PTGER2/PKA axis, facilitating entry into a PKA-dominant rather than AKT-dominant cellular state. We propose the use of PGE2 for in vitro decidualization as an alternative to 8-Br-cAMP. Abstract : In vitro decidualization of human endometrial stromal fibroblasts with PGE2 and progestin induces a different but genuine decidual cell state through PTGER2-dependent PKA activation when compared to the conventional cyclic AMP/MPA protocol. Graphical Abstract: